Trivial Homology Groups of Warped Product Semi-Slant Submanifolds in Kenmotsu Space Forms - Noura M. Alhouiti; Ali H. Alkhaldi; Akram Ali; Fatemah Mofarreh; Piscoran Laurian-Ioan (Axioms)
This paper investigates the relationship between homology groups and warped product semi-slant submanifolds in Kenmotsu space forms. Some rigidity theorems for vanishing homology groups on warped product semi-slant submanifolds are obtained using the moving-frame method and the second fundamental form inequality. Our results are an extension of previous studies in this direction.